Short‐ and long‐term survival has improved after radical cystectomy for bladder cancer in Québec during the years 2000‐2015. Issue 8 (28th March 2019) - Wissing, Michel D.; Santos, Fabiano; Zakaria, Ahmed S.; O'Flaherty, Ana; Tanguay, Simon; Kassouf, Wassim; Aprikian, Armen G.
Abstract: Background and Objectives: We evaluated the short‐ and long‐term outcome in bladder cancer (BC) patients treated with radical cystectomy (RC) in Québec (Canada). Methods: Data were collected from provincial registries on all BC patients who underwent RC in Québec province in 2000‐2015. Outcomes were hospitalization rates and survival. Survival analyses were conducted using log‐rank tests and Cox proportional hazards models. Results: In total, 4450 patients were included in our analysis. RC was increasingly conducted by higher‐volume surgeons in larger, higher‐volume, academic hospitals. Comparing patients treated in 2010‐2015 to 2000‐2009, recently treated patients had shorter postoperative hospital stays (absolute difference, 0.9 days, P  < 0.001) but also a higher readmission rate (25.0% vs 21.1% in the 30 days following discharge, P  = 0.003). Overall (5‐year rates 50.9% vs 42.7%, P  < 0.001) and BC‐specific survival (61.3% vs 55.5%, P  < 0.001) had significantly improved. In multivariable analyses, overall survival was significantly better in recently treated patients (hazard ratio [HR], 0.66; 95% confidence interval [CI], 0.60‐0.73), younger patients (HR, 1.16; 95% CI, 1.14‐1.19), patients residing closer to the hospital (HR, 1.03; 95% CI, 1.01‐1.06), and patients treated by high‐volume surgeons (HR, 0.88; 95% CI, 0.82‐0.94). Conclusions: Survival in BC patients after RC has improved in recent years. Other predictors for survival are younger age, shorter distance between patients' residences and hospitals, and higher surgeon's RC loads.